2023
DOI: 10.1021/acs.nanolett.3c03103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of γ-Cyclodextrin-Reduced Fe(III) Nanoparticles with Peroxidase-like Catalytic Activity for Bacteriostasis of Food

Xiaohui Liu,
Yuhan Zhao,
Yuanhong Xu
et al.

Abstract: Foodborne pathogens are a primary cause of human foodborne illness, making it imperative to explore novel antibacterial strategies for their control. In this study, Fe-γ-CD was successfully synthesized as a food antibacterial agent for use in milk and orange juice. The Fe-γ-CD consists of 6/11 Fe­(II) and 5/11 Fe­(III), which catalyze a Fenton-like catalytic reaction with H2O2 to generate •OH. Consequently, Fe-γ-CD exhibits exceptional peroxidase-like activity and broad-spectrum antibacterial efficacy. Fe-γ-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The protein leakage of MRSA upon exposure to TFBZ was determined by BCA quantifying. As described in Supplementary Figure S1B , the protein in the cell-free supernatant exposed to an increased TFBZ concentration (0–4 μg/mL) exhibited a persistent, significant and dose-dependent leakage within 12 h ( Liu et al, 2023 ) These results indicated that TFBZ could disrupt the integrity of cell membrane, and destruct the growth and metabolic balance of MRSA, which ultimately contributing to bacterial death.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The protein leakage of MRSA upon exposure to TFBZ was determined by BCA quantifying. As described in Supplementary Figure S1B , the protein in the cell-free supernatant exposed to an increased TFBZ concentration (0–4 μg/mL) exhibited a persistent, significant and dose-dependent leakage within 12 h ( Liu et al, 2023 ) These results indicated that TFBZ could disrupt the integrity of cell membrane, and destruct the growth and metabolic balance of MRSA, which ultimately contributing to bacterial death.…”
Section: Resultsmentioning
confidence: 85%
“…Equal volume of bacteria mixture was taken out at different time intervals (0, 4, 8, and 12 h) and centrifuged for 10 min. The protein content was determined by the Enhanced BCA Protein Assay Kit (Beyotime, Shanghai, China) and corresponding protein concentration was extrapolated from the equation of best-fit linear regression line of the BCA standard curve ( Liu et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…(b) Preparation of γ-CD-reduced Fe­(III) nanoparticles for bacteriostasis of food. Reproduced with permission from ref . (c) A photoresponsive host–guest complex for controlling plant bacterial diseases.…”
Section: Applications In Synergistic Bacterial Inhibitionmentioning
confidence: 99%
“…Liu and co-workers developed Fe-based γ-CD nanoparticles (Fe-γ-CD), with a predominant concentration of Fe­(II) and a few Fe­(III), possessing peroxidase-like activity for decomposing H 2 O 2 into ROS. Antibacterial experiments revealed that Fe-γ-CD was active against both Gram-negative bacteria and the mature biofilms of Gram-positive bacteria (Figure b) . Huang, Li, and co-workers fabricated a pH-responsive double-layer indicator film based on chitosan/curcumin-β-CD complex/cinnamaldehyde and zein/alizarin (CS/Cur-β-CD/CIN-Z/AL) with enhanced antioxidant and antibacterial properties for pork freshness monitoring and maintaining …”
Section: Applications In Synergistic Bacterial Inhibitionmentioning
confidence: 99%
“…Rapid evolution of bacterial resistance and sluggish discovery of new antibiotics are compelling researchers to develop novel and potent bactericidal drugs. Nanozyme-mediated catalytic antibacterial therapy (NCAT) is becoming prevalent and considered to be a promising alternative to antibiotics. As a type of enzyme-mimicking nanomaterials, nanozymes, such as peroxidase (POD) and oxidase (OXD)-like, exert bacterial inactivation through catalyzing reaction substrates to generate highly toxic reactive oxygen species (ROS). Especially, NCAT would rarely induce antimicrobial resistance, due to the distinct biocidal mechanism of causing irreversible oxidative damage inside bacteria. , Over several years, many strategies have been proposed to boost the catalytic performance of nanozymes to obtain satisfactory NCAT, including surface functionalization, defect engineering, structure modulation, and exogenous field stimulus. Especially, light irradiation is widely applied to excite photoresponsive/catalytic nanozymes toward largely increased ROS levels, owing to the advantages of easy operation and spatiotemporal controllability. However, constrained by the large band gap, most photocatalytic nanozymes could only absorb ultraviolet or visible light that possesses quite shallow tissue penetration, being detrimental to their practical bioapplications. Moreover, only nanozymes with an appropriate conduction band (CB) have the capacity to drive the half-reaction for improving ROS generation efficiency, which restricts energy utilization and causes ineffective harvesting.…”
Section: Introductionmentioning
confidence: 99%